Factors Affecting Food Consumption Behaviors of Elderly in Makham Tia, Mueang District, Surat Thani Province - Yakoh, Kameelah (JOURNAL OF SOUTHERN TECHNOLOGY, 2017)
The objectives of this cross sectional descriptive study were to study the food consumption behaviors of elderly and investigate factors influencing food consumption behaviors of elderly in Makham Tia, Mueang district, Surat Thani province. The subject was composed of 226 elderly people using simple random sampling. The data were collected using questionnaires and then analyzed to obtain percentage, means, standard deviation, Chi-square and Pearson’s.Product.Moment Correlation Coefficient. The results showed that (1) Food consumption behaviors of elderly were at a moderate level (78.38%). Personal factors include gender, age, status, educational level, living status, occupation, source of income, income, sufficiency of income, health condition and dental care had not correlated with food consumption behaviors. (2) Predisposing factors including food consumption knowledge was at a high level (70.27%) and had weak positive relationship with food consumption behaviors (r=0.130) whereas attitude toward food consumption was at a high level (72.07%) and had significant positive relationship with food consumption behaviors (r= 0.206, P<.01). (3) Enabling factors were at a moderate level (58.56%) and were significantly weak negative correlated with food consumption behaviors (r= -0.155, P<.05). (4) Reinforcing factors were at a moderate level (72.52%) and were significantly positive correlated with food consumption behaviors (r= 0.258, P<.01). The findings suggest that good preliminary data can be used to health care plan development for promoting healthy food consumption behaviors to achieve a better quality of life in terms of healthy and sustainability.